2010
DOI: 10.1016/j.ejpain.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

An observational study on the effect of S(+)‐ketamine on chronic pain versus experimental acute pain in Complex Regional Pain Syndrome type 1 patients

Abstract: The data indicate that while ketamine's effect on acute experimental pain is driven by pharmacokinetics, its effect on CRPS pain persisted beyond the infusion period when drug concentrations were below the analgesia threshold for acute pain. This indicates a disease modulatory role for ketamine in CRPS-1 pain, possibly via desensitization of NMDAR in the spinal cord or restoration of inhibitory sensory control in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 32 publications
2
45
0
1
Order By: Relevance
“…The skin on the volar side of the forearm was stimulated by heat. Ketamine had a dose-dependent antinociceptive effect (Sigtermans et al, 2010). No significant effect of NSAID alone, but increases in sensation and pain tolerance thresholds were seen for the combination tramadol plus diclofenac.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The skin on the volar side of the forearm was stimulated by heat. Ketamine had a dose-dependent antinociceptive effect (Sigtermans et al, 2010). No significant effect of NSAID alone, but increases in sensation and pain tolerance thresholds were seen for the combination tramadol plus diclofenac.…”
mentioning
confidence: 88%
“…Conclusions. Sigtermans et al (2010) concluded from their study in patients suffering from chronic complex regional pain syndrome type 1 that ketamine's effect on acute pain is plasma concentration-driven, displaying an on-off effect, and involves inhibition of NMDA receptors involved in the processing of acute pain. NMDA receptors are important players in the plasticity seen in chronic pain.…”
Section: Wilder-smith Et Al (1998) Pharmacology Of Human Pain Modelsmentioning
confidence: 99%
“…IV ketamine had a morphine-sparing effect after orthopaedic surgery, and also facilitated rehabilitation at one month and decreased postoperative chronic pain up to six months after surgery [26]. It was suggested that while S(+)ketamine's effect on acute experimental pain was driven by pharmacokinetics, its effect on chronic pain persisted beyond the infusion period when drug concentrations were below the analgesia threshold for acute pain, indicating a modulatory role for ketamine in chronic pain states [27]. Ketamine also enhances the descending inhibiting serotoninergic pathway, exerts antidepressive effects and analgesia persists for plasma concentrations ten times lower than hypnotic concentrations [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, R(-)-and S(+)-Ketamine metabolites were described as analgesics through action at α7-nicotinic acetylcholine receptor, which may contribute to the final analgesic effect [30]. In addition, systemically administered ketamine has been described to have local aesthetic and anti-inflammatory actions such as inhibition of transcription factors activator protein 1 and nuclear factor-kappa-B, interleukin-8 production, as well as CD11b and CD16 expression, as well as spinal effects possibly involving desensitization of NMDA receptors in the spinal cord or restoration of inhibitory sensory control in the brain [15,27,31]. N-methyl-Daspartate receptors also are located peripherally on sensory afferent nerve endings, and this provided the initial impetus for exploring peripheral applications of ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike high-dose opioid analgesics, respiratory depression is not seen with ketamine. & Clinical trials to date have been limited, but recently published studies have addressed three forms of ketamine treatment: intravenous subanesthetic dosing [67,68], intravenous high-dose anesthesia ("ketamine coma") [69], and topical administration [70•]. Although intravenous ketamine is used routinely by anesthesiologists intraoperatively as an anesthetic agent, its use in treating CRPS is considered off-label.…”
Section: Spinal Cord Stimulationmentioning
confidence: 99%